Urban Myths about Learning and Education - De Bruyckere, Pedro; Kirschner, Paul Arthur, 1951-; Hulshof, Casper D. (London, UK : Academic Press, 2015)
Are boys better in math than girls? Do we really only use 10% of our brains? Urban Myths about Learning and Education debunks the most common myths in education and learning and gives a concise overview of the proof behind the reality. Along the way, the authors discuss why these myths are so entrenched in the public consciousness and what can be done to retrain parents, teachers, policy makers, and the public to know better. This well-researched yet concise and light-hearted book discusses myths regarding what we learn, how we learn it, how we retain it, how the brain works, myths about education and technology, and myths relating to educational policy.
The big clear-out -- Myths about learning -- Neuromyths -- Myths about technology in education -- Myths in educational policy -- Myth persistence and myth busting.
Print version record.
Includes bibliographical references and index.
Keywords: Education; Educational change; EDUCATION -- Essays; EDUCATION -- Organizations & Institutions; EDUCATION -- Reference; Education; Educational change; Electronic books